2022
DOI: 10.3389/fviro.2021.792659
|View full text |Cite
|
Sign up to set email alerts
|

HTLV-1's Foxy Strategy for Survival and Transmission

Abstract: Human T-cell leukemia virus type 1 (HTLV-1) is the causative agent of adult T-cell leukemia-lymphoma (ATL) and inflammatory diseases including HTLV-1-associated myelopathy (HAM). A remarkable feature of HTLV-1 is that this virus transmits primarily through cell-to-cell contact. HTLV-1 increases the number of infected cells in vivo to ensure its survival and transmission. Therefore, survival of HTLV-1-infected cells in vivo is very critical for transmission under the host immune surveillance. HTLV-1 possesses m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Therefore, increasing Nrp1 expression might represent a second mechanism by which HBZ enhances TGF-β signaling. This signaling pathway is implicated in establishing the regulatory T-cell-like phenotype documented for most HTLV-1 infected cells [ 84 ]. It would be interesting to investigate this, and other potential effects of Nrp-1 related to HTLV-1 infection and pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, increasing Nrp1 expression might represent a second mechanism by which HBZ enhances TGF-β signaling. This signaling pathway is implicated in establishing the regulatory T-cell-like phenotype documented for most HTLV-1 infected cells [ 84 ]. It would be interesting to investigate this, and other potential effects of Nrp-1 related to HTLV-1 infection and pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…However, because Tax exhibits strong immunogenicity, infected T cells expressing Tax are actively eliminated by Tax-specific CTLs [22,23]. At the onset of ATL, approximately 50% of cases do not show Tax expression due to methylation or the deletion of the 5 LTR region; thus, the selective proliferation of clones that are not attacked by CTLs is likely to be promoted [24]. In addition, recent studies have revealed that sense-side transcription leading to Tax expression occurs in transient bursts, even in the absence of genomic deletions or epigenetic changes in the provirus [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, HTLV-1 is involved in the development of a variety of autoimmune diseases and several other inflammatory diseases, such as bronchiectasis, arthritis, infective dermatitis, myopathies, and multiple different uveitides ( 6 , 7 ). HTLV-1 is transmitted in various routes such as blood transfusion, intravenous injection, sexual contact, vertical transmission from mother to baby, breastfeeding, and organ transplant ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%